AN EVALUATION OF A SELF-REGULATORY APPLICATION FOR THE EFFECTIVE MANAGEMENT OF STUDENTS’ STUDY HABITS - Oliha, Festus O.; Usiobaifo, A, R. (FUDMA Journal of Sciences, 2024)
The academic performance of a student has a connection with his or her study habits. Existing research indicates that there is inadequate assessment of technology-based self-directed strategies implemented in self-study applications for effective management of students’ learning habits. In this study, the case-based approach was adopted in the design of ‘Study Pal’, a self-regulatory mobile application implemented with strategies outlined in the Zimmerman cyclic model – forethought, performance, and reflection stages. An evaluation of the solution for efficacy recorded an 89% success rate using the cloud-based semi-automated tool – TestRail. The findings suggest that it is very effective at enhancing student study habits through self-regulated learning (SRL) strategies, guiding students in planning, executing, and reflecting on their study activities to develop good academic performance and higher self-regulation. It therefore confirms technological involvement in the capacity of SRL apps to enhance and assess students’ study habits. Consequently, the study’s findings not only contribute to the existing pool of knowledge in the domain but also foster motivation and engagement among students leading to improved academic performances. On the other hand, the study shades concern on the reflection features implemented which may benefit from additional features to improve the overall study outcome.